PENGARUH CORPORATE GOVERNANCE TERHADAP AGRESIVITAS PAJAK DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Dewi Kusuma Wardani; Agnesia Jeni Dodok (FEB Universitas Maritim Semarang, 2022)
This study aims to find empirical evidence about the effect of corporate governance on tax aggressiviness with the disclosure of corporate social responsibility as a moderating variable seen from the financial statements listed on the IDX. The sampel data is 193 annual financial reports in 2016-2020. The analysis was carried out using multiple linear regression analysis and Moderated Regression Analysis (MRA) with the SPSS version 21 program. Based on the results of data analysis and discussion conducted, it can be concluded that corporate governance has a positive effect on tax aggressiviness. Corporate social responsibility can weaken the negative influence of corporate governance on tax aggressiveness.